STRATEGY TO FORM STUDENTSPOSITIVE MOTIVATIONTOEDUCATIONAL AND PROJECT PROFESSIONAL ACTIVITIES - Vitkovskaya, Irina; Solovyeva, Tatiana; Ovchinnikova, Aleksandra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The article presents the authors’ strategy for the formation of positive motivation of students to educational and project professional activities, based on students’ project activities structuring and management at different hierarchical levels. For each level (academic discipline, main professional educational program, faculty, university, region, country) the authors propose various forms of project implementation, the content of which meets modern school challenges, professional community requirements and contributes to the transformation of the diffuse nature of students’ needs towards professional motives.In the course of the research, both theoretical methods (pedagogical literature analysis, modeling) and empirical methods (pedagogical experiment, questionnaire) were used.The basis for the experimental part of the study was made by 1st year students of Pskov State University, taking the course “Pedagogical Education”, studying the discipline “Introduction to Pedagogical Activity” that is built on the basis of a project-oriented program.An important educational effect of the presented strategy implementation was the growth of motives for professional self-realization, improvement of the emotional background of students’ motivation for professional activity, awareness of the subjective need for active interaction, as well as the acquisition of certain educational skills related to project activities and useful for teachers’ successful work.